Contra Horowitz: A Case for Reparations to Blacks for Slavery - Jon-Paul Amos; Walter E. Block (Međunarodne Studije, 2022)
Horowitz rejects reparations for African Americans. We demonstrate that their heirs are entitled to the property illegitimately obtained by the slave owners. When we operate under the libertarian homesteading principle, the land should be redistributed back to the people who worked and tilled it first. That is, the black slaves. Horowitz’s claims against reparations serve as a poor refutation towards the reparations argument. African Americans are entitled to the “40 acres and a mule” that was promised, yet never fulfilled. We rely upon libertarian theory to clearly understand the case for reparations.